Measurement in Scientific Research - Asmar, Hassan; Mohammed, Murad (Humanities Journal of University of Zakho, 2023)
The purpose of this paper is to highlight the importance of measurement in scientific research, with an emphasis on measurement in social research and the progress it has made, as well as, the differences in views in the social sciences on the need for measurement. To explain measurement, scale-related concepts such as reality, validity, certainty, accuracy, objectivity and intersubjectivity are highlighted, as these concepts directly affect the measurement process and scale creation. The understanding of measurement in the natural sciences differs from the social sciences. Measurement in the natural sciences was found to be more advanced than in the social sciences. While the purpose of measurement is to produce some kind of truth, but it may sometimes not be able to measure the entire object or component intended to measure, therefore, we may reach wrong conclusions, and the measurement may appear at a lower level than expected.